First report of naturally infected Aedes aegypti with chikungunya virus genotype ECSA in the Americas - Costa-da-Silva, André Luis; Ioshino, Rafaella Sayuri; Petersen, Vivian; Lima, Antonio Fernando; Cunha, Marielton dos Passos; Wiley, Michael R.; Ladner, Jason T.; Prieto, Karla; Palacios, Gustavo; Costa, Danuza Duarte; Suesdek, Lincoln; Zanotto, Paolo Marinho de Andrade; et al. (PLOS Neglected Tropical Diseases, 2017)
Author summary The chikungunya outbreaks have become one of the main public health problems in the Northeast Region of Brazil. Since the chikungunya virus (CHIKV) was recently introduced in this country, finding vector associations involved in its transmission to the vertebrate host is primordial to better design efficient intervention against mosquitoes. In the present study, field-caught mosquitoes in Aracaju city, Sergipe State, Brazil were evaluated for the presence of CHIKV and other two endemic arboviruses (Zika and Dengue viruses) in this region. We described here the first identification of the East-Central-South-African (ECSA) CHIKV genotype naturally infecting Aedes aegypti mosquitoes in Brazil. This work suggests the involvement of this species in CHIKV outbreaks in Northeast Region of this country and reveals a possible interaction between this vector and the recently introduced CHIKV ECSA genotype.